2018
DOI: 10.1159/000489626
|View full text |Cite
|
Sign up to set email alerts
|

MiR-142-3p Enhances Cell Viability and Inhibits Apoptosis by Targeting CDKN1B and TIMP3 Following Sciatic Nerve Injury

Abstract: Background/Aims: MiRNAs are involved in phenotype modulation of neural cells after peripheral nerve injury. However, the roles of miRNAs on the survival of dorsal root ganglion (DRG) neurons have not yet been fully understood. Methods: In this study, the expression of miR-142-3p was measured in rat DRGs (L4-L6) during the initial 24 hours post sciatic nerve transection by microarray profiling and quantitative PCR. The functional assays including the cell viability, colony formation, cell cycle and apoptosis as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…For example, Bao et al found that miR-142-3p promoted endothelial cell proliferation via Bcl-2-associated transcription factor 1 [41]. In addition, Wu et al found that miR-142-3p promoted the neuronal cell cycle and inhibited apoptosis after peripheral nerve injury [42]. Thus, further investigation, especially the appropriate animal model studies, of microRNAs involved in the regulation of cell growth should be performed to clarify these issues.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bao et al found that miR-142-3p promoted endothelial cell proliferation via Bcl-2-associated transcription factor 1 [41]. In addition, Wu et al found that miR-142-3p promoted the neuronal cell cycle and inhibited apoptosis after peripheral nerve injury [42]. Thus, further investigation, especially the appropriate animal model studies, of microRNAs involved in the regulation of cell growth should be performed to clarify these issues.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous investigations have shown that miRNAs play a vital role in PNI and peripheral nerve repair; for instance, the expression of miRNAs in dorsal root ganglia (DRG) tissues after sciatic nerve injury in rats was significantly changed ( Li et al, 2012 ). miR-142-3p can target CDKN1B and TIMP3 to enhance the viability of rat DRG neurons and inhibit apoptosis after sciatic nerve injury ( Wu D.M. et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…MiRNA participates in biological processes in human organism mainly by regulating the expression of its target genes [30,31]. Dong-Mei Wu et al shown that miR-142-3p can partially promote the neuronal cell cycle and inhibit cell apoptosis by inhibiting CDKN1B and TIMP3 expressions [32]. In this study, the miR-221-3p mimic down-regulated CDKN1B level, while miR-221-3p inhibitor up-regulated CDKN1B level.…”
Section: Discussionmentioning
confidence: 46%